First pass uptake of 14C-propranolol by the lung. - Geddes, D M (1979)
Uptake of 14C-propranolol by the lungs during a single passage through the pulmonary circulation was measured in ten patients at cardiac catheterisation. Mean lung uptake of propranolol was 75% in seven patients who were not previously taking the drug and 33% in three patients who were taking it as regular oral treatment. Lung uptake of propranolol in man is therefore considerable and is partly saturable by normal oral doses. This may alter the dose response relation for propranolol and a wide range of other drugs when given intravenously. The method used to study lung uptake is simple and might be suitable for studies of endothelial cell function in disease.